A Flexible Framework for Evaluating Cyber Security Maturity and Risks in Electric Power Generation Organizations - Lima, Milton de; Cruz Junior, Geraldo da; Cunha, David da; Barreto, Jimmy Paul Souza (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2024)
This study proposes a novel framework for assessing the maturity of adaptive cybersecurity measures to enhance overall cybersecurity resilience and mitigate related risks. The framework’s validity was confirmed by developing and testing a Minimum Viable Product (MVP) in collaboration with cybersecurity experts from the power generation industry. Feedback from all experts affirmed that the framework effectively addresses the cybersecurity requirements and operational protocols inherent to the power generation sector.